Rotator Cuff Reconstruction Using Fascia Lata Patch Autograft for the Nonrepairable Rotator Cuff Tear - Matthewson, Graeme (Arthrosc Tech, 2020)
A large to massive rotator cuff tear is a common issue that lacks reliable options to return a patient's range of motion and function when conservative treatment has failed. With up to 96% of massive rotator cuff repairs failing within the first 6 months of repair, surgeons have been searching for a reliable treatment option for this difficult subset of patients. Surgical options for massive, retracted rotator cuff tears include re-establishing the counterforce coupling of the rotator cuff with techniques such as a partial repair or superior capsular reconstruction, preventing superior humeral migration as seen with balloon spacer implantation, and eliminating pain generators with techniques such as biceps tenotomy; however, these do not reconstitute dynamic cuff control. More recently, an acellular dermal allograft, as seen in superior capsular reconstruction, has been used to reconstruct the remaining rotator cuff. We describe a technique using a fascia lata autograft to reconstruct the rotator cuff in the setting of a massive cuff tear. This is of particular importance in centers that lack the funding or institutional approval to use acellular dermal allografts that have been popularized to date.